Hubungan Komunikasi Efektif Pada Staff Front Office Di Bagian Pendaftaran Dengan Kepuasan Pasien Rawat Jalan Di X Hospitals Balikpapan - Chrisdayanti, Mitha; Marchamah, Dwi Nur Siti; Arumsari, Wahyuni (Indonesian Journal of Health Community, 2025)
Communication is important for establishing relationships, especially in the healthcare industry. particularly for front office staff who are the first point of contact for patients. In March 2024, X Hospitals Balikpapan received 168 reviews with one out of five rating on Google Customer Reviews. The common complaint was the lack of communication by the front office staff. This research aims to determine the relationship between effective communication among front office staff at registration department and outpatient satisfaction at X Hospitals Balikpapan The research utilized a correlational analytic approach with a cross-sectional design, encompassing a sample of 96 outpatients out of 45,985 population at the polyclinic from April to June 2024, using a quota sampling technique. The data analysis included univariate and bivariate analysis. The results revealed that 49% of respondents perceived the communication of front office staff as effective, and 49% reported satisfaction with the services provided. The correlation analysis using Kendall's Tau-B yielded a coefficient of 0.427 with a significance value of 0.000, indicating a significant relationship between effective communication by front office staff and outpatient satisfaction. Based on these results, it is recommended that the hospital enhance front office staff's communication skills by providing training.